Penerapan Perangkap Lipat (Traps) untuk Penangkapan Kepiting Bakau (Scylla sp.) di Kabupaten Aceh Barat Provinsi Aceh - Hafinuddin Hafinuddin; Uswatun Hasanah (Jurnal Marine Kreatif, 2017)
Prospect of fishing business of mud crab has became the right choice because demand of mud crab is increasing and market price is relatively good. The availability mud crab for local market in West Aceh District is affected by minimum catch, unefficient fishing, where fishermen is still using traditional fishing gear i.e. scoop net as well as having internal factor and external factor. Because of that, the potential business for mud crab fishing with eco-friendly fishing gear i.e. traps is very good to applied. Applying traps was carried out at Kuala Bubon Village Samatiga Sub district Aceh Barat District Aceh Province. Applying traps is for pilot project for fisherman. The Methods include 1) mentoring and sosialization traps; 2) training for making traps and 3) operating traps. Result of the activity show 1) fish catching using traps is better than using scoop net; 2) increased skilll  for fishermen about making traps and 3) increased understanding for fisherman about using eco-friendly fishing gear to catching mud crab. Applying traps for fisherman community is very potential to developed for mud crab fishing business.